Outcomes of a NYC Public Hospital System Low-Threshold Tele-Buprenorphine Bridge Clinic at 1 Year. (1st June 2022) - Tofighi, Babak; McNeely, Jennifer; Yang, Jenny; Thomas, Anil; Schatz, Daniel; Reed, Timothy; Krawczyk, Noa
Abstract: Background: This study evaluated clinical outcomes of a low barrier tele-buprenorphine bridge program for NYC residents with opioid use disorder (OUD) at 1 year during the coronavirus disease 2019 (COVID-19) pandemic. Methods and materials: This retrospective analysis of the NYC Health + Hospitals (NYC H + H) Virtual Buprenorphine Clinic registry assessed baseline demographic and clinical characteristics, rates of referrals to community treatment, and induction-related adverse events among city residents with OUD, from March 2020 to the end of March 2021. Results: The program enrolled 199 patients, of whom 62.3% were provided same-day visits (n = 124). Patients were enrolled in the program for a median of 14 days (range 0-130 days). Referrals sources included hospital and clinic staff (n = 83, 47.7%), word of mouth (n = 30, 17.2%), and correctional health or reentry services (n = 30, 17.2%). Induction-related adverse events were mostly limited to precipitated withdrawal symptoms (n = 21, 5%). Roughly half of patients were referred to community treatment (n = 109, 54.8%) and of those 51.4% (n = 56/109) completed at least one visit in community treatment. Discussion: Our experience indicates that a low threshold tele-buprenorphine bridge program in place of a safe and feasible approach to facilitating entry in community treatment for underserved people who use opioids in a large metropolitan area.